Tahap amalan kepimpinan pengajaran dalam kalangan guru besar sekolah rendah - Satu kajian di Daerah Penampang - Saruji, Saidi (2010)
This research attempted to study the level of principals' instructional leadership at primary school in Penampang, Sabah. A total of 12 schools and 273 respondents were selected for the purpose of this study. The "Principal Instructional Management Rating Scale" (PIMRS) was used, as its survey instruments, to measure the instructional leadership practice among the principals. The instruments registered a reliability of Cronbach's Alpha 0.9783. All of the questionnaires were returned completely. The data were analyzed using the "Statistical Package For Social Sciences" (SPSS) software, version 12.0 to work out the descriptive method of frequency, mean, percentage and the inference method Pearson Correlation. Results show that, higher (mean=4.04) and moderate (mean=3.64) levels of principals' instructional leadership are highly significance towards the high and moderate achievement in UPSR results but low level of principals' instructional leadership are not significance to the UPSR result. Also, Pearson Correlation shows that the principals' instructional leadership is positively significance (r=.23, P<0.05) to the achievement in UPSR results